Dielectric polarization effect and transient relaxation in FAPbBr3 films before and after PMMA passivation. Issue 17 (23rd April 2021) - Guo, Yongchang; Zou, Bingsuo; Yang, Fan; Zheng, Xuan; Peng, Hui; Wang, Jianping
Abstract : In organic–inorganic hybrid lead halide perovskites with a naturally arranged layered structure, the dielectric polarization effect caused by the dielectric mismatch between the organic and inorganic layers takes effect in their optical responses. Abstract : In organic–inorganic hybrid ionic lead halide perovskites with a naturally arranged layered structure, the dielectric polarization effect caused by the dielectric mismatch between the organic and inorganic layers takes effect in their optical responses. But this effect has received little attention. Here we used infrared transient spectroscopy to study FAPbBr3 perovskite polycrystalline films before and after PMMA film passivation and found that there is a dielectric polarization effect at the interface between the organic cation layer and the inorganic lattice layer inside the perovskite lattice, and also at the interface between the PMMA film and perovskite film. Due to the dielectric polarization effect and the spatial confinement of the surface electronic (or polaron) state, the luminescence intensity of the passivated perovskite film is significantly enhanced, and the exciton lifetime is greatly increased. Dielectric polarization enhances their efficient transient absorption (TA) and leads to the intramolecular vibration frequency red-shifts, which exhibited the combined relaxation kinetics of the large polaron with dielectric polarization in the perovskite film. Dielectric polarization between the internal lattice and the nanocrystal surface of the perovskite film shows different relaxation processes. The polarization-dependent TA spectrum reveals that the dielectric polarization field causes light-induced anisotropy by changing the chemical bond configurations. These direct TA experimental observations help us to understand the influence of the dielectric polarization effect on the electronic state in various organic–inorganic nanocomposite perovskites.